2012
DOI: 10.1016/j.matbio.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tissue biomechanics and mechanical signaling in uterine leiomyoma

Abstract: Leiomyoma are common tumors arising within the uterus that feature excessive deposition of a stiff, disordered extracellular matrix (ECM). Mechanical stress is a critical determinant of excessive ECM deposition and increased mechanical stress has been shown to be involved in tumorigenesis. Here we tested the viscoelastic properties of leiomyoma and characterized dynamic and static mechanical signaling in leiomyoma cells using three approaches, including measurement of active RhoA. We found that the peak strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 58 publications
(76 reference statements)
4
103
0
Order By: Relevance
“…Desmin is a type III intermediate filament expressed by skeletal, smooth, and cardiac muscle tissue (25). The leiomyoma is composed by an abnormal ECM (11). Thus, cells, exposed to different viscoelastic forces, continue to grow and proliferate (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desmin is a type III intermediate filament expressed by skeletal, smooth, and cardiac muscle tissue (25). The leiomyoma is composed by an abnormal ECM (11). Thus, cells, exposed to different viscoelastic forces, continue to grow and proliferate (26).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal extracellular matrix (ECM) protein expression, and increased growth factors, cytokines and chemokines leading to disorganized ECM are involved in the development and growth of uterine leiomyomas (10). Modifications of the ECM, its viscosity and elasticity, may change the intercellular communication by determining an increased mitotic activity (11). Mechanical signals are transmitted by the receptor from the ECM to the cytoskeleton, in order to maintain an isometric state and structural organization of a default (12 GTPase protein, appears to be part of a mechano-regulatory circuit that could modify the interactions between proteins of the cytoskeleton by inducing leiomyoma growth (13).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, there is strong evidence that the ECM directly stimulates intercellular signaling. Because of the abnormal composition, structure, fluid content and stiffness of the tumor, there is increased tissue tension (153). This increased tissue tension and stretch induces mechanical signaling transmitted from collagen and other fibers in the ECM to intracellular components through transmembrane receptors including integrins and cadherins (153,154).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Because of the abnormal composition, structure, fluid content and stiffness of the tumor, there is increased tissue tension (153). This increased tissue tension and stretch induces mechanical signaling transmitted from collagen and other fibers in the ECM to intracellular components through transmembrane receptors including integrins and cadherins (153,154). This complex mechanical signaling network involves alterations in cell shape and cytoskeleton in addition to altered stiffness and ECM (155).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Several studies have shown that tumor growth is not only regulated by the malignancy of the tumor cells, but is also associated with several factors that are present in the tumor microenvironment, including cytokines, electrolytes and other secreted proteins (8). The IF flow movement may influence the degree of viscosity and elasticity of the ECM, thus modifying the intercellular communication and determining an increased mitotic activity (9). Collagen and other proteoglycans such as lumican (LUM) induce the activation of the integrin signaling pathway, which serves a key role in cytoskeleton reorganization, cell motility and proliferation (6).…”
Section: Introductionmentioning
confidence: 99%